N-oleoylethanolamine − phosphatidylcholine complex loaded, DSPE-PEG integrated liposomes for efficient stroke - Xiangrui Yang (Taylor & Francis Group, 2021)
Causing more and more deaths, stroke has been a leading cause of death worldwide. However, success in clinical stroke trials has remained elusive. N-oleoylethanolamine (OEA) was an endogenous highly hydrophobic molecule with outstanding neuroprotective effect. In this article, hydrogen bonds were successfully formed between OEA and soybean phosphatidylcholine (SPC). The synthetic OEA-SPC complex and DSPE-PEG were self-assembled into liposomes (OEA NPs), with OEA-SPC loaded in the core and PEG formed a hydrophilic shell. Hence, highly hydrophobic OEA was loaded into liposomes as amorphous state with a drug loading of 8.21 ± 0.18 wt%. With fairly uniform size and well-distributed character, the OEA NPs were systemically assessed as an intravenous formulation for stroke therapy. The results indicated that the administration of OEA NPs could significantly improve the survival rate and the Garcia score of the MCAO rats compared with free OEA. The TTC-stained brain slices declared that the cerebral infarct volume and the edema degree induced by MCAO could be decreased to an extremely low level via the administration of OEA NPs. The Morris water maze (MWM) test suggested that the spatial learning and memory of the MCAO rats could also be ameliorated by OEA NPs. The immunofluorescence assay stated that the apoptosis of the neurons and the inflammation within the brain were greatly inhibited. The results suggest that the OEA NPs have a great chance to develop OEA as a potential anti-stroke formulation for clinic application.